Enhancing the Integrity of Evidence-Based Medicine: A Literature Review on Reporting Quality in Systematic Reviews and Randomised Controlled Trials - Woźniak, Łukasz; Lompart, Albert; Wabiszczewicz, Michał; Kosarewicz, Albert; Krysiak, Patrycja (Quality in Sport, 2025)
This literature review synthesises evidence on reporting quality and integrity in evidence-based medicine (EBM). It critically examines challenges undermining the trustworthiness of systematic reviews (SRs) and randomised controlled trials (RCTs) and explores solutions and frameworks to address these issues. Based on 22 selected academic articles, including reviews, guidelines, studies, and opinions, the analysis highlights themes like reporting standards (PRISMA, CONSORT, SPIRIT), appraisal tools (GRADE, AMSTAR), technology (AI, telehealth, electronic data), and expert collaboration. Findings show a gap between reporting guidelines and practice, causing a “trustworthiness crisis”. Despite guideline adoption, poor reporting, data issues, and bias persist. Key solutions include involving information science experts to refine searches, using AI and automation to boost efficiency and spot integrity issues, adopting new tools like Evidence Gap Maps (EGMs), and improving trial design with Decentralised Clinical Trials (DCTs). Strengthening EBM’s integrity needs more than guideline compliance: it demands a cultural shift towards transparency, combined with methodological rigour, technology, and interdisciplinary collaboration. Only this integrated approach ensures that clinical and policy decisions rest on the most robust and credible evidence possible.